DEIXIS ANALYSIS IN THE SHORT STORY THE WOMAN WHO LOST IN THE PATCHOUMI GARDEN - Sukma Adelina Ray; Asri Yulianda (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This study analyzes the function of deixis (person, place, and time) in the short story